Indoor air quality in arid areas - Konstantinos E. Kakosimos (9863975) (2025)
Indoor air quality (IAQ) in arid regions faces unique challenges, including dust infiltration, reliance on energy-intensive cooling systems, and inadequate filtration technologies. This study examines the factors contributing to compromised IAQ, such as particulate matter from dust storms and cultural practices like incense burning, while highlighting innovative solutions like biodegradable air filters, passive cooling designs, and advanced insulation. Through a synthesis of recent studies, it underscores the need for tailored policies, technological advancements, and community engagement to address IAQ challenges and enhance health outcomes in arid environments. Other Information Published in: Current Opinion in Environmental Science & Health License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.coesh.2025.100610